English Substantive and procedural aspects of disinheritance under the Slovak law: English - Raková, Karin; Lowi, Alexandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The basic principle of Slovak succession law is based on the autonomy of the deceased to dedicate on the distribution of his property or its part to a certain person after his death. The deceased is practically free to choose his heirs and the distribution of his property, as testamentary freedom is one of the most fundamental principles of succession law. The only restriction on testamentary freedom is given to the forced heirs, who are entitled to a compulsory portion in the event that the testator omitted them in his will or when they got less than their compulsory portion was.Slovak law recognises the only way in which the testator has the right to exclude his forced heir from inheriting the obligatory share based on the statutory ground of disinheritance.Disinheritance is considered to be a strictly formal legal act of the testator, by which he exclude his descendant from the legal right of inheritance. A person who has been validly disinherited by the testator shall not be entitled to any inheritance or obligatory share.In order for the testator to achieve what he intended by such an act and for his will to be valid, it must comply with the formal and substantive requirements of the law. The grounds for disinheritance are defined in Article 469a Sect. 1a) – d) of the Civil Code (hereinafter the "CC" or „Civil Code“). For the validity of the legal act of disinheritance, the formal and substantive requirements of disinheritance must be met and cannot vary from the legal grounds stated in the law. The purpose of the paper will be to provide with the analysis of the substantive conditions for the disinheritance under Article 469a Sect. 1a) – d) of the Civil Code, and on the basis of the analysis of selected court decisions to summarize the current court practice in this respective field. The paper also analyses the procedural aspects of disinheritance disputes, which mostly results in the proceedings before the court.
Keywords: English